THE UNIQUE ASPECTS OF ABU MANSUR AL-MATURIDI’S WORKS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
It is well-known that the Maturidite doctrine is one of the two main theological schools in the Islamic world. The widespread acceptance and prominence of this school are undoubtedly due to the significant influence of Abu Mansur al-Maturidi’s works. Two of his main works have reached us: Kitab al-Tawhid, which is devoted to the creed of Ahl al-Sunnah, and his Qur'anic exegesis titled Ta’wilat Ahl al-Sunnah. In this tafsir as well, the verses of the Qur’an are primarily interpreted from a theological perspective. These two works served as the cornerstone of the Maturidite theological school. Therefore, understanding Maturidite theology and its unique features begins with the study of Imam al-Maturidi’s writings. To properly comprehend and grasp the essence of any work, it is of utmost importance to understand its writing style and methodology.